Narratives in Political Advertising: An Analysis of the Political Advertisements in the 2014 Midterm Elections. Issue 2 (3rd April 2018) - Vafeiadis, Michail; Li, Ruobing; Shen, Fuyuan
Abstract : This study examined the use of narrative political advertisements during the 2014 midterm elections. A content analysis of 243 ads identified three narratives types: autobiographical, voter stories, and testimonials. Narrative ads were mostly positive and focused almost equally on issues and candidates' characters. Negative attack ads and anonymous announcers were primarily used by candidates who lost the election, whereas winners employed more often autobiographical spots and included family members in the ads. The growing use of narratives in political advertising as found in the present study suggests that future research should further examine the effects of narrative political ads on individuals.